If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 4x = -3x + 43 Reorder the terms: -6 + 4x = 43 + -3x Solving -6 + 4x = 43 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -6 + 4x + 3x = 43 + -3x + 3x Combine like terms: 4x + 3x = 7x -6 + 7x = 43 + -3x + 3x Combine like terms: -3x + 3x = 0 -6 + 7x = 43 + 0 -6 + 7x = 43 Add '6' to each side of the equation. -6 + 6 + 7x = 43 + 6 Combine like terms: -6 + 6 = 0 0 + 7x = 43 + 6 7x = 43 + 6 Combine like terms: 43 + 6 = 49 7x = 49 Divide each side by '7'. x = 7 Simplifying x = 7
| 90=3(8x+6) | | 5(x+4)+3=9x+5(x+3) | | 8n=7(2n+7) | | 1-6(-2x-6)=109 | | R^2+12r-66=-6 | | -4/7=?/28 | | ln(7x)=81 | | (X+2)-4-6x=3x+10 | | 91=-7(7-4k) | | 14=z-y | | -5n-7=23 | | Cosx=2sinx | | -6-6x=1x+4 | | 14a^2+7a-196=0 | | 355=-5n-5(8n-8) | | 2cos^2x+5sinx-5=0 | | 1/9=?/45 | | (X+2)-2(4-3x)=2(x+4)-4 | | (-7)-x=-5 | | 9n^2+94n-168=0 | | 7x-8=55-2x | | (-3)-x=2 | | p-12=218 | | .5x^2=8 | | -6a=36a | | y=2x-5x+7 | | 2.9r=-5.7t-5 | | x-(-14)=-11 | | 5y-9=7+y | | 60-what+10=20 | | 5=1-4(-5) | | 3m-7=m-13 |